Joint Source and Channel Decoding for Variable Length Encoded Turbo Codes - Liu, Jianjun; Tu, Guofang; Zhang, Can; Yang, Yang (EURASIP journal on advances in signal processing, 2008)
Joint source and channel decoding (JSCD) has been proved to be an effective technique which can improve decoding performance by exploiting residual source redundancy. Most previous publications on this subject focus on a traditional coding scheme in which the source variable-length coding (VLC) is serially concatenated with a channel code. In this paper, a parallel concatenated coding scheme for the VLC combined with a turbo code is presented. By merging a symbol-level VLC trellis with a convolutional trellis, we construct a symbol-level joint trellis with compound states. Also, a solution of the symbol-by-symbol a posteriori probability (APP) decoding algorithm based on this joint trellis is derived, which leads to an iterative JSCD approach in the similar way to the classical turbo decoder. The simulation results show that our joint source-channel en/decoding system achieves some gains at the cost of increasing decoding complexity, when compared to the joint iterative decoding based on the bit-level super trellis for the separate coding system.